Engaging teachers in lifelong learning in Oman for knowledge growth and development: government roles and higher institutions - Amzat, Ismail Hussein; Al-Mahruqi, Salim Hamed; Teslikhan, Muhajir; Al Omairi, Turkiya (Springer, 2017)
Lifelong learning (LLL) remains widely discussed in today literature as a mechanism to keep updated with the latest information and knowledge. Engaging in LLL is a necessity for teachers to stay current, alerted with the changes in education, and remain on the cutting edge in the field of teaching. To keep up with new developments, it takes courage and self-determination to continue learning. Through teacher professional development (TPD), continuous learning and improvement can take place via professional training, workshops, conferences and personal reading to upgrade teaching skills, content knowledge and classroom teaching practices. Teachers are believed and empirically proven to influence student achievement. As far as student achievement is concerned, teachers’ continuous learning and constant improvement are inevitable. Again, studies have evidenced that teacher engagement in continuous learning benefits both teaching and learning. Inasmuch as TPD is considered as a vehicle for teacher improvement, teacher engagement in lifelong learning (LLL) can be perceived as a driver that drives that particular vehicle where new knowledge and skills are obtained. Besides, when teachers involve in LLL, this helps them to develop continuous learning mind-set and habit which as a result will facilitate innovation and creativity among teachers. It prepares teachers with the assistance of continuous training to face the challenges, and keeps teachers up to date on new research and methods of teaching twenty-first-century learners using new technology to enrich teaching as well as facilitate learning in the classroom. With this scenario, this research sets out to explore the level of teacher engagement in lifelong learning activities in Sultanate of Oman. Besides, it aims of identifying government and educational institutions roles in Oman in empowering teachers towards lifelong learning for continuous professional development (CPD) for best practices. Some empirical data were collected from teachers’ lived-experiences about LLL for TPD in Oman. The findings are expected to play a pivotal role in urging Omani government and educational institutions to create a learning environment in which teachers and students becoming lifelong learners as well as where developing cultural learning mind-sets can be nurtured. It is envisaged that the findings will emphasize the need of government and education institutions’ roles in fostering lifelong learning among teachers throughout their lives.